Characterizing tumor microenvironment heterogeneity in EBV+ nTNKL vs ENKTL using spatial transcriptomics and MIF - Qian, Siyu; Wang, Zeyuan; Zhang, Yue; Zhao, Wanyue; Qiao, Honghan; Feng, Xiaoyan; Duan, Yukai; Su, Boyuan; Hao, Shifeng; Yang, Zhenzhen; Zhang, Mingzhi; Chen, Qingjiang; et al. (Frontiers in Immunology, 2026)
BackgroundEpstein–Barr virus (EBV)-positive nodal T/NK-cell lymphoma (EBV+ nTNKL) has recently been delineated in the WHO-HAEM5 classification as a distinct and exceptionally rare entity. Its biology and clinical trajectory remain obscure relative to Extranodal NK/T-cell lymphoma (ENKTL).MethodsWe applied spatial transcriptomics and multiplex immunofluorescence to representative ENKTL and EBV+ nTNKL specimens, integrating these data with a retrospective clinical cohort of 14 EBV+ nTNKL patients—constituting one of the largest series described to date.ResultsSpatial transcriptomics revealed fundamental differences between ENKTL and EBV+ nTNKL. ENKTL, of NK-cell origin, displayed higher malignant cell density, neutrophil enrichment, and an immune-desert phenotype, whereas EBV+ nTNKL, of T-cell origin, showed reduced tumor burden, B-cell enrichment, and an immune-active microenvironment with abundant cytotoxic T cells and PD-1/PD-L1 expression. Intercellular communication analyses further highlighted distinct signaling programs—TGF-β/BMP-driven tumor–neutrophil interactions in ENKTL versus CXCL/CCL–GPCR-mediated macrophage crosstalk in EBV+ nTNKL. In a retrospective cohort of 14 EBV+ nTNKL patients, the disease was frequently complicated by hemophagocytic lymphohistiocytosis and conferred significantly inferior survival, although selected patients achieved durable responses with immune checkpoint inhibitors or CAR-T therapy.ConclusionThis study delineates the immunologic and molecular architectures of ENKTL and EBV+ nTNKL, providing rare insights into this understudied lymphoma. Despite limited sampling, these findings underscore the central role of EBV latency programs and tissue context in shaping tumor ecology and suggest avenues for subtype-tailored therapeutic strategies.